고압처리가 발아벼의 화학성분 변화에 미치는 영향 - 김민영(Min Young Kim); 이상훈(Sang Hoon Lee); 장귀영(Gwi Yeong Jang); 박혜진(Hye Jin Park); 윤나라(Nara Yoon); 이연리(Youn Ri Lee); 이준수(Junsoo Lee); 정헌상(Heon Sang Jeong) (한국식품과학회지, 2015)
This study was performed to evaluate changes in the chemical composition of germinated rough rice with high hydrostatic pressure treatment (HPT). Rough rice was germinated at $37^{°}C$ over 6 days (control), and then subjected to HPT at 30 MPa for 24 h. The highest crude protein content was 9.54% in the control sample after 6 days of germination. Crude lipid content increased from 2.04-2.74% (control) to 2.27-3.10% (HPT). HPT samples showed higher values of total free sugar and glucose content than those of the control. The total amino acid value was not significant, but the essential amino acid content increased from 0.45-5.09 mg/g in the control to 1.57-5.30 mg/g in the HPT sample. The major fatty acids were found to be palmitic, oleic, and linoleic acid. The content of oleic acid decreases with HPT, whereas that of linoleic and linolenic acid increased slightly during the initial stages of germination. These results suggest that HPT after germination efficiently depolymerizes chemical components and enhances the content of essential nutrients. 본 연구는 발아와 고압처리 시간에 따른 발아벼의 일반성분, 유리당, 유리아미노산 조성 및 지방산 조성을 분석하여 화학성분 변화에 미치는 고압처리의 효과에 대해 연구하였다. 조단백질과 조지방 함량은 30 MPa 압력에서 24시간 고압처리 시 발아 일수에 따라 각각 8.39-9.59% 범위로 대조구에 비해 증가하였다. 유리당 함량은 발아와 고압처리에 의해 총 유리당 함량과 glucose 함량은 증가하였으나 maltose와 fructose 함량은 감소하였다. 총 아미노산 함량은 고압처리에 의해 유의적인 차이를 나타내지 않았지만 필수아미노산 함량은 고압처리 시 1.57-5.34 mg/g 범위로 대조구인 0.45-5.09 mg/g에 비해 증가하였다. 주요 지방산은 oleic acid와 linoleic acid가 가장 많았으며, 특이적으로 linoleic acid가 발아 및 고압처리에 의해 유의적으로 증가하였다. 본 연구결과 발아와 고압의 병행처리 시 발아벼의 영양성분이 저분자화 되고 필수영양성분이 증가함을 알 수 있었으며, 이러한 결과는 고부가가치의 식품소재 개발을 위한 기초자료로 활용할 수 있을 것으로 판단된다.